The isolation of water-soluble natural products – challenges, strategies and perspectives. Issue 3 (14th October 2021) - Berlinck, Roberto G. S.; Crnkovic, Camila M.; Gubiani, Juliana R.; Bernardi, Darlon I.; Ióca, Laura P.; Quintana-Bulla, Jairo I.
Abstract : The isolation of water-soluble metabolites significantly diminished during the last decades. A comprehensive analysis on the isolation of hydrophilic natural products is discussed with a perspective for the future of natural product sciences. Abstract : Covering period: up to 2019 Water-soluble natural products constitute a relevant group of secondary metabolites notably known for presenting potent biological activities. Examples are aminoglycosides, β-lactam antibiotics, saponins of both terrestrial and marine origin, and marine toxins. Although extensively investigated in the past, particularly during the golden age of antibiotics, hydrophilic fractions have been less scrutinized during the last few decades. This review addresses the possible reasons on why water-soluble metabolites are now under investigated and describes approaches and strategies for the isolation of these natural compounds. It presents examples of several classes of hydrosoluble natural products and how they have been isolated. Novel stationary phases and chromatography techniques are also reviewed, providing a perspective towards a renaissance in the investigation of water-soluble natural products.